EZH2 cooperates with gain‐of‐function p53 mutants to promote cancer growth and metastasis. (5th February 2019) - Zhao, Yu; Ding, Liya; Wang, Dejie; Ye, Zhenqing; He, Yundong; Ma, Linlin; Zhu, Runzhi; Pan, Yunqian; Wu, Qiang; Pang, Kun; Hou, Xiaonan; Weroha, Saravut J; et al.
Abstract: In light of the increasing number of identified cancer‐driven gain‐of‐function (GOF) mutants of p53, it is important to define a common mechanism to systematically target several mutants, rather than developing strategies tailored to inhibit each mutant individually. Here, using RNA immunoprecipitation‐sequencing (RIP‐seq), we identified the Polycomb‐group histone methyltransferase EZH2 as a p53 mRNA‐binding protein. EZH2 bound to an internal ribosome entry site (IRES) in the 5′UTR of p53 mRNA and enhanced p53 protein translation in a methyltransferase‐independent manner. EZH2 augmented p53 GOF mutant‐mediated cancer growth and metastasis by increasing protein levels of mutant p53. EZH2 overexpression was associated with worsened outcome selectively in patients with p53‐mutated cancer. Depletion of EZH2 by antisense oligonucleotides inhibited p53 GOF mutant‐mediated cancer growth. Our findings reveal a non‐methyltransferase function of EZH2 that controls protein translation of p53 GOF mutants, inhibition of which causes synthetic lethality in cancer cells expressing p53 GOF mutants. Synopsis: In addition to its well‐established oncogenic roles as SET‐domain containing polycomb‐group family member, EZH2 is here shown to promote cap‐independent translation of p53 GOF mutant mRNA to drive prostate cancer progression, possibly explaining the paradoxical EZH2 deletion observed in various malignancies. EZH2 binds to the 5′UTR IRES site of p53 mRNA in human prostate cancer cells independent of its methyltransferase activity. EZH2 interacts with eIF factors and increases p53 mRNA binding with polysomes. Depletion of EZH2 decreases p53 mRNA expression and protein stability in vitro and in a prostate cancer in vivo model. Expression of EZH2 and p53 positively correlate in human cancers. EZH2 depletion induces synthetic vulnerability and inhibits growth in p53 GOF mutant‐expressing cancer cells and tumors in vivo . Abstract : A non‐methyltransferase function of EZH2 controls cap‐independent translation of wildtype and mutant p53 in prostate cancer.